Time in maps - Wigen, Kären,Winterer, Caroline (The University of Chicago Press, 2020)
Foreword /Abby Smith Rumsey –Introduction : Maps tell time /Caroline Winterer and Kären Wigen –Mapping time in the twentieth (and twenty-first) century /William Rankin –Part I:Pacific Asia.Orienting the past in early modern Japan /Kären Wigen –Jesuit maps in China and Korea : connecting the past to the present /Richard A. Pegg –Part II:The Atlantic World.History in maps from the Aztec empire /Barbara E. Mundy –Lifting the veil of time : maps, metaphor, and antiquarianism in the seventeenth and eighteenth centuries /Veronica Della Dora –A map of language /Daniel Rosenberg –Part III:The United States.The first American maps of deep time /Caroline Winterer –How place became process : the origins of time mapping in the United States /Susan Schulten –Time, travel, and mapping the landscapes of war /James R. Akerman.
9780226718590
Keywords: Konferenzschrift; Cartography; Time in cartography; Conference papers and proceedings